Activity of Imipenem-Relebactam against Carbapenem-Resistant Escherichia coli Isolates from the United States in Relation to Clonal Background, Resistance Genes, Coresistance, and Region - Johnston, Brian D. (Antimicrob Agents Chemother, 2020)
Imipenem-relebactam (I-R) is a recently developed carbapenem–beta-lactamase inhibitor combination agent that can overcome carbapenem resistance, which has now emerged in Escherichia coli, including sequence type 131 (ST131) and its fluoroquinolone-resistant H30R subclone, the leading cause of extraintestinal E. coli infections globally. To clarify the likely utility of I-R for carbapenem-resistant (CR) E. coli infections in the United States, we characterized 203 recent CR clinical E. coli isolates from across the United States (years 2002 to 2017) for phylogroup, clonal group (including ST131, H30R, and the CTX-M-15-associated H30Rx subset within H30R), relevant beta-lactamase genes, and broth microdilution MICs for I-R and 11 comparator agents. Overall, I-R was highly active (89% susceptible), more so than all comparators except tigecycline and colistin (both 99% susceptible). I-R’s activity varied significantly in relation to phylogroup, clonal background, resistance genotype, and region. It was greatest among phylogroup B2, ST131-H30R, H30Rx, Klebsiella pneumoniae carbapenemase (KPC)-positive, and northeast U.S. isolates and lowest among phylogroup C, New Delhi metallo-β-lactamase (NDM)-positive, and southeast U.S. isolates. Relebactam improved imipenem’s activity against CR isolates within each phylogroup—especially groups A, B1, and B2—and particularly against isolates containing KPC. I-R remained substantially active against isolates coresistant to comparator agents, albeit somewhat less so than against the corresponding susceptible isolates. These findings suggest that I-R should be useful for treating most CR E. coli infections in the United States, largely independent of coresistance, although this likely will vary in relation to the local prevalence of specific E. coli lineages and carbapenem resistance mechanisms.